Physics for geologists - Chapman, Richard E. (Taylor & Francis, 2002)
This up-dated edition discusses a wide range of forces at work in geology against the background of Kepler's and Newton's laws; electromagnetic radiation from optics to gamma rays, atomic structure and age-dating.
Keywords: Geology.; Physics.; elektronické knihy; electronic books